Exploring EFL teachers' technological pedagogical content knowledge (tpack) in digital classrooms - Bajuri Sahnan; Sholihatul Hamidah Daulay; Maslathif Dwi Purnomo (Indonesian Counselor Association (IKI), 2025)
This study explores the application of the Technological Pedagogical Content Knowledge (TPACK) framework among English as a Foreign Language (EFL) teachers within digital classroom environments. As educational technology continues to reshape language teaching, it becomes essential to understand how EFL teachers integrate technological, pedagogical, and content knowledge in their instructional practices. Using a qualitative research design, this study employed in-depth semi-structured interviews with 30 EFL teachers from diverse educational institutions. The findings reveal nuanced patterns in teachers’ integration of TPACK components, shaped by factors such as access to professional development, institutional support, individual attitudes toward technology, and contextual barriers unique to EFL digital classrooms. Notably, the study highlights inconsistencies in TPACK application, with many teachers demonstrating strong pedagogical or content knowledge but struggling with technological integration. These insights contribute to a deeper understanding of TPACK implementation in digitally mediated language instruction and underscore the need for targeted support in teacher education programs. The study concludes by offering recommendations for professional development that address the evolving demands of digital language teaching and proposes directions for future research across broader educational contexts